Seed dormancy and germination of Halophila ovalis mediated by simulated seasonal temperature changes - Statton, J.; Sellers, R.; Dixon, Kingsley; Kilminster, K.; Merritt, D.; Kendrick, G. (Academic Press, 2017)
© 2017 Elsevier Ltd The seagrass, Halophila ovalis plays an important ecological and sediment stability role in estuarine systems in Australia with the species in decline in many sites. Halophila ovalis is a facultative annual, relying mainly on recruitment from the sediment seed bank for the annual regeneration of meadows. Despite this, there is little understanding of seed dormancy releasing mechanisms and germination cues. Using H. ovalis seed from the warm temperate Swan River Estuary in Western Australia, the germination ecology of H. ovalis was investigated by simulating the natural seasonal variation in water temperatures. The proportion of germinating seeds was found to be significantly different among temperature treatments (p < 0.001). The treatment with the longest period of cold exposure at 15 °C followed by an increase in temperature to 20–25 °C (i.e. cold stratification) had the highest final mean germination of 32% and the fastest germination rate. Seeds exposed to constant mean winter temperatures of 15 °C had the slowest germination rate with less than two seeds germinating over 118 days. Thus temperature is a key germination cue for H. ovalis seeds and these data infer that cold stratification is an important dormancy releasing mechanism. This finding has implications for recruitment in facultative annual species like H. ovalis under global warming since the trend for increasing water temperatures in the region may limit seed-based recruitment in the future.